EVALUASI PELAKSANAAN PERATURAN DAERAH NO. 8 TAHUN 2009 TENTANG KAWASAN TANPA ASAP ROKOK DAN KAWASAN TERTIB ROKOK DI KOTA PADANG PANJANG (Studi Kasus pada RSUD Kota Padang Panjang) - Revi Abdullah; Febri Yuliani (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2016)
Health is an important aspect of Human Rights (HAM) and capital for the successful development of a nation. Because without health implementation of a comprehensive national development and will not be fully realized. One of the Local Government in Indonesia who have been seriously address the issue of smoking is Padang Panjang. Padang Panjang is the first city in West Sumatra to implement smoke-free areas. Exactly on March 17, 2009 Date of Padang Panjang issued Local Regulation of the Regions and Regions Without Smoke Cigarettes tongue ie Regulation No. 8 of 2009. The purpose of the enactment of this area is to protect public health from the dangers of smoking, cultivate healthy life, suppress growth figures novice smokers. Hospital Padang Panjang included into the category health service stated in Bylaw No. 8 Year 2009 on Regions Without Smoke in Padang Panjang where the implementation of this regulation is not maximized implemented in hospitals of environmental Padang Panjang and also sanctions were not running. The purpose of this study was to evaluate the implementation of this regulation and also to determine factors - factors that affect the implementation of this regulation in the Padang Panjang City Hospital.This research was conducted in hospitals Padang Panjang using qualitative descriptive method. Data collection is done by observation and in-depth interviews of various informants that have been determined. Qualitative research, the data obtained from primary and secondary sources. In analyzing the data of all the information gathered to learn that a conclusion can be drawn into a coherent whole that is the result of research. This research was conducted by using the theory according to William N. Dunn on policy evaluation with the evaluation criteria: effectiveness, efficiency, adequacy, responsiveness, equity, accuracy.Results of this study can be concluded that the evaluation criteria, effectiveness, efficiency, adequacy, responsiveness, equity, accuracy. The implementation of these regulations has not run optimally and also sanctions were not yet firm. Furthermore, the factors that affect the implementation of this regulation that institutional factors and socio-cultural factors.Keywords: Evaluation of Regional Regulation Regions Without Smoke, Factors Affecting Implementation of the Regulation